P027: Emergency medical services (EMS) assist-requiring hypoglycemia in Southwest Ontario. (2nd June 2016) - Peddle, M.; Liu, S.; Reid, H.; Columbus, M.; Mahon, J.; Dukelow, A.; Spaic, T.
Abstract : Introduction: Hypoglycemia is a common treatment consequence in diabetes mellitus (DM) and the second most common cause of Emergency Department (ED) visits for adverse drug events. Prior studies have examined the rates of ED visits and inpatient hospitalizations for hypoglycemia. These represent only a small proportion of severe hypoglycemic events, as many do not present to hospital. To date, there have been no Canadian population-based studies examining the rates of EMS assist-requiring hypoglycemia in DM patients in the pre-hospital setting. The objective of this study was to determine the prevalence and describe the EMS assist-requiring hypoglycemia in DM patients in Southwestern Ontario.Methods: A population-based retrospective cohort study was conducted on all EMS calls for diabetic emergency from 2008-2014 in Southwestern Ontario, Canada. Data was extracted from the electronic ambulance call records for 11 EMS services in the region.Results: There were 9, 265 EMS calls for a diabetic emergency (mean age 59 ± 20 years, 57% male, 82% DM). For 223 calls (2.4%) patients were younger than 19 years of age. The mean blood glucose level on presentation was 2.49 ± 1.02 mmol/L and 2, 116 (24%) call subjects had initial GCS score less than 9. Treatment (intravenous glucose or IM glucagon) was given in 7, 126 (77%) calls. There were 3, 884 (51 %) hypoglycemia episodes with documented insulin use and 1, 436 (19 %) documented oral hypoglycemia agents use. Between 2008 and 2014, rates of calls increased by 7.4% (p<0.0001). Prevalence of hypoglycemia calls during the study period was estimated at 189 per 10, 000 diabetes patients per year. In 2, 297 (24.8%) instances, the patient refused transport to the ED.Conclusion: The rates of EMS assist-requiring hypoglycemia are almost double the rates of hospitalization/ED visits for acute DM complications in our region. Many life threatening episodes of hypoglycemia may go unreported and subsequently not followed by the patient's primary health care provider. Further assessment and proper education following those episodes may help decrease the rate of severe hypoglycemia.